Synthesis of novel cyano quinoline derivatives - Okten, Salih; Cakmak, Osman (PERGAMON-ELSEVIER SCIENCE LTD, 2015)
6,8-Dibromo-1,2,3,4-tetrahydroquinoline (2) and 3,6,8-tribromoquinoline (3) were converted into the corresponding cyano derivatives via copper assisted nucleophilic substitution reactions. While bromination of 6-bromo-8-cyanotetrahydroquinoline (11) gave 3,6-dibromo-8-cyanoquinoline (8), the reaction of dicyano-1,2,3,4-tetrahydroquinoline (12) resulted in the formation of an unexpected dimer (15). (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Quinoline; Bromo quinoline; Cyano quinoline; Bromination; MEK MAPKK INHIBITORS; FRIEDLANDER SYNTHESIS; EFFICIENT; Chemistry